The Role of General and Daily Control Beliefs for Affective Stressor-Reactivity Across Adulthood and Old Age - Koffer, Rachel (J Gerontol B Psychol Sci Soc Sci, 2019)
Background: General and situational control beliefs have been examined separately as buffers of the effects of daily stressors on affective well-being. However, general (trait) control beliefs reflect perceived ability to adapt, change, and influence overall life circumstances, whereas situational (daily) control beliefs reflect perceived ability to manage current circumstances and achieve desired outcomes. Method: Using 9 weeks of daily reports from 150 adults aged 18–89 years, we examined the extent that general and daily control beliefs buffer the between- and within-person associations involving stressors and negative and positive affect (i.e., daily stress processes) and whether/how the extent of buffering differs with age. Results: Aligning with prior findings, both greater average stressor exposure and experiencing a daily stressor compromised daily affective well-being and both higher general and daily control beliefs facilitated daily affective well-being. Specific to the motivating hypotheses, both general and daily control beliefs buffered daily stressor-reactivity. Age was associated with individuals’ daily stressor-buffering, such that stressor-reactivity was more effectively damped at older ages. Associations between general control beliefs and daily stress processes were age invariant. Discussion: Mixed evidence of age differences across general and daily control beliefs highlights how within-person processes may differentially contribute to well-being as individuals accommodate age-related strengths and vulnerabilities.